1984
DOI: 10.1111/j.1749-7345.1984.tb00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Cage Culture of Red Tilapia in Prawn and Shrimp Ponds

Abstract: Feeding trials were conducted in prawn ponds (freshwater) and shrimp ponds (brackishwater) with red tilapia stocked in floating 0.8‐m3 cages. Pond sizes ranged from 0.23 to 0.45 ha. Seven ponds were stocked at a density of 26 cages/ha. One hundred 9‐9 tilapia fingerlings were stocked into each cage. Fish survival after 8 weeks averaged 98.5% excluding a set of six cages from one pond which was preempted from the study due to high mortality, possibly caused by algal toxins. The growth of caged tilapia fed suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 9 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Nile tilapia, Oreochromis niloticus, have the ability to filter-feed on phytoplankton (Perschbacher and Lorio 1993;Turker et al 2003aTurker et al , 2003b) and, concomitantly, produce a second crop of marketable animal in polyculture systems (Dos Santos and Valenti 2002). Tilapia and freshwater prawn have been shown to be good complimentary species (Brick and Stickney 1979;Rouse and Stickney 1982;Meriwether et al 1984;Rouse et al 1987;Gracia-Perez and Alston 2000;Dos Santos and Valenti 2002). reported that polyculture of free-swimming tilapia in prawn ponds increased economic returns by 21%.…”
mentioning
confidence: 99%
“…Nile tilapia, Oreochromis niloticus, have the ability to filter-feed on phytoplankton (Perschbacher and Lorio 1993;Turker et al 2003aTurker et al , 2003b) and, concomitantly, produce a second crop of marketable animal in polyculture systems (Dos Santos and Valenti 2002). Tilapia and freshwater prawn have been shown to be good complimentary species (Brick and Stickney 1979;Rouse and Stickney 1982;Meriwether et al 1984;Rouse et al 1987;Gracia-Perez and Alston 2000;Dos Santos and Valenti 2002). reported that polyculture of free-swimming tilapia in prawn ponds increased economic returns by 21%.…”
mentioning
confidence: 99%
“…The high mortality rate of the 40 ppt treatment was compensated by the higher weights of the three surviving fish, which significantly differed from the mean final weights of the other treatments (p < 0.05)., Better growth performance at higher salinity (brackish water and seawater) was first documented in red tilapia which was associated with reduced aggressive behavior [5,11,44,45] . Finally, the tolerance of Nile tilapia to salinity fluctuations after long-term exposure to high salinity becomes more apparent, such as when there is a need to re-acclimate them back to freshwater for breeding purposes, as shown by the zero mortality of samples, including the three fish that survived 40 ppt.…”
Section: Discussionmentioning
confidence: 99%
“…Although tilapia and freshwater prawns have been shown to be good complimentary species (Brick & Stickney 1979;Rouse & Stickney 1982;Meriwether et al 1984;Rouse et al 1987;Dos Santos & Valenti 2002), Uddin et al (2007a) observed that gut content analysis showed that both species strongly preferred phytoplankton above zooplankton when in polyculture, and there was considerable overlap in their food preferences. An important factor influencing the compatibility of prawn-fish interactions is the size of animals stocked.…”
Section: Fish and Prawn Interactionsmentioning
confidence: 99%